Left-sided gallbladder (Sinistroposition) encountered during laparoscopic cholecystectomy: A rare case report and review of the literature. - Zoulamoglou, Menelaos; Flessas, Ioannis; Zarokosta, Maria; Piperos, Theodoros; Papapanagiotou, Ioannis; Birbas, Konstantinos; Konstantinou, Evangelos; Mariolis-Sapsakos, Theodoros (Int J Surg Case Rep, 2017)
INTRODUCTION: True Left-sided gallbladder (LSG) is a rare anatomical variation with a prevalence of 0.3%. Mainly discovered during the operation, its surgical approach in the laparoscopic setting may be challenging even for an experienced surgeon. PRESENTATION OF CASE: LSG was unexpectedly discovered in a young man during laparoscopic cholecystectomy. There were no pre-operative indications of this sinistroposition. The laparoscopic cholecystectomy was performed with minor surgical modifications and it was uneventful. A meticulous review of recent literature about LSGs was conducted as well. DISCUSSION: LSG is a scarce anatomical aberration that is difficultly identified pre-operatively. Surgeons should be aware of this aberration and of its accompanying anatomical variations in order to perform a safe laparoscopic cholecystectomy. CONCLUSION: Surgeons, by placing the patient to left-side up position, are able to expose the Calot's triangle and possible accompanying anatomical anomalies and thus perform a safe laparoscopic cholecystectomy without difficult surgical modifications.